In Peskin & Schroeder's QFT, if we set $$|p\rangle = \sqrt{2E_p} a^{\dagger}_p|0\rangle \tag{2.35}$$ as in equation 2.35, then how do I get to the next equation 2.36:

$$\langle p|q\rangle = 2E_p (2\pi)^3 \delta^3(p-q) \tag{2.36} $$ Where I seem to be stuck is: $$\langle p|q\rangle =\sqrt{2E_p 2E_q}\langle0|a_pa_q^{\dagger}|0\rangle $$ I don't understand why $\langle0|a_pa_q^{\dagger}|0\rangle$ is prop. to the delta function.


Try commuting $a_p$ and $a_q^\dagger$ and keep in mind that $a_n|0\rangle = 0$.

  • $\begingroup$ so I get $\sqrt{2E_p2E_q} \langle 0 |a_p a_q^{\dagger}|0\rangle = \sqrt{2E_p2E_q} \langle 0 |[a_p ,a_q^{\dagger}]|0\rangle + \sqrt{2E_p2E_q} \langle 0 |a_q^{\dagger} a_p |0\rangle $. The second term is zero since $a_n |0\rangle = 0 \forall n$. So we get, using $[a_p, a_q^{\dagger}] = 1 $, $\sqrt{2E_p2E_q} \langle 0 |0\rangle$. But what is $\langle 0 |0\rangle$ equal to? Thank you $\endgroup$ – laguna Oct 23 '17 at 7:59
  • 3
    $\begingroup$ Depending on whether you have Bosonic or Fermionic operators, the bracket inside the first term after the $=$ sign is either a commutator or an anti-commutator. But, regardless, that bracket is a the delta function. So you have: $\sqrt{4E_pE_q}\langle 0|\delta^3(q - p)(2\pi)^3|0\rangle = \sqrt{4E_pE_q}\delta^3(q - p)(2\pi)^3\langle 0|0\rangle= \sqrt{4E_pE_q}\delta^3(q - p)(2\pi)^3 = $ the desired answer. $\endgroup$ – IcyOtter Oct 23 '17 at 8:09
  • $\begingroup$ Thank you. And by definition $\langle s | s \rangle = 1$ for all states $s$, right? $\endgroup$ – laguna Oct 23 '17 at 8:20
  • 1
    $\begingroup$ No problem! And yes, for any normalised state, we have $\langle s|s\rangle = 1$. In other words, a state projects onto itself 100%. $\endgroup$ – IcyOtter Oct 23 '17 at 10:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.